Work overload, role conflict, interpersonal relationship and work stress among employees in Majlis Agama Islam Selangor (MAIS) / Nurul Nadhirah Che Din and Ummu Nabilah Muhamad Paudzi - Che Din, Nurul Nadhirah; Muhamad Paudzi, Ummu Nabilah (2022)
This study aims to investigate the factors that lead to work stress among employees in Majlis Agama Islam Selangor (MAIS). Stress is defined as a feeling of being overwhelmed, worrying, destruction, pressure, and tiredness that can negatively impact people’s wellbeing. Thus, stress can cause a person to experience both physical and psychological health problem, particularly among working people. Work overload, role conflict, and interpersonal relationships were the factors highlighted in this study. The study adopted questionnaires from past studies in measuring stress and its related factors. Using the systematic sampling technique, a self-administered online survey was distributed and 150 respondents participated in the study. The study indicates that work overload, role conflict and interpersonal relationships have a positive significant relationship with the level of stress experienced by employees. Thus, the study identified that the dominant factor that lead to work stress among employees in MAIS is work overload shows moderate positive relationship with the value of the correlation recorded at r=0.751.